2022
DOI: 10.3389/fmed.2022.872658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optic Disc Ovality Index and Rotation Angle Measurements in Myopic Eyes Using Photography and OCT Based Techniques

Abstract: PurposeTo compare optic nerve head (ONH) ovality index and rotation angle measurements based on semi-automated delineation of the clinical ONH margin derived from photographs and automated BMO configuration derived from optical coherence tomography (OCT) images in healthy and glaucomatous eyes with high-, mild- and no axial myopia.MethodsOne hundred seventy-five healthy and glaucomatous eyes of 146 study participants enrolled in the Diagnostic Innovations in Glaucoma Study (DIGS) with optic disc photographs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Additionally, it has been suggested that AL is a better indicator of eye size than SE. 45 Furthermore, it is worth exploring the possibility of a mechanical or physical relationship between eye movements and AL. This relationship warrants further investigation to determine the exact cause and underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested that AL is a better indicator of eye size than SE. 45 Furthermore, it is worth exploring the possibility of a mechanical or physical relationship between eye movements and AL. This relationship warrants further investigation to determine the exact cause and underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Spectralis OCT, Rezapour et al found a torsion angle of 34.4° (range 29.9 to 39.0) vs. 33.7° (range 27.6 to 39.9) in mild myopia (mean AXL of 24.8 mm, range 24.7 to 25.0) vs. high myopia (mean AXL of 26.8 mm, range 26.6 to 27.0). In addition, they obtained no association between the photograph-based and OCT-based assessment of the torsion angle in high-axial myopic eyes ( p ≥ 0.33 with R 2 = 0.03 from 0.0 to 0.21) [ 33 ]. It should be highlighted that these different torsion angle values are due to the fact that the OCT-based torsion angle is a BMO-based assessment while the photographed-based torsion angle is measured relative to the clinical disc margin, which does not always correspond with the BMO, especially in myopic eyes.…”
Section: Optic Nerve Head Torsionmentioning
confidence: 99%
“…Torsion angle 34.4° (range 29.9 to 39.0) vs. 33.7° (range 27.6 to 39.9) in mild 24.8 mm (range 24.7 to 25.0) vs. high 26. 8 mm (range 26.6 to 27.0) myopic eyes [ 33 ]…”
Section: Figurementioning
confidence: 99%
“…Several reports have investigated the relationship of myopic refractive error and/or axial length (AXL) with individual ONH parameters measured from OCT images in healthy myopic eyes. 8 10 , 21 26 Myopic ONH structural changes that may be associated with connective tissue remodeling is more directly influenced by myopic AXL elongations. 2 , 27 Furthermore, most of these ONH parameters are well correlated with each other, and it is unclear which ONH parameters are independently associated with longer AXL.…”
mentioning
confidence: 99%